FACTORS INHIBITING THE IMPLEMENTATION OF THE ROAD MAP POLICY FOR BUREAUCRATIC REFORM AT THE INSTANTIONAL LEVEL (Study at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province) - Reski Melyana Melamba (Faculty of Law, Universitas Pekalongan, 2023)
Reforming the Indonesian bureaucracy is a long-term agenda that continues to be the focus of every government. Bureaucratic reform policy is a process to change processes, public bureaucratic procedures and the attitudes and behavior of bureaucrats to achieve bureaucratic effectiveness and national development goals (Quah, 2022). The bureaucratic reform agenda in Konawe Regency has been going on for 8 (eight) years. During these eight years, dynamics and complexity have colored the steps and movements of bureaucratic reform in the Regional Government of Konawe Regency, Southeast Sulawesi Province. However, unfortunately, until now, or entering the final stage, the implementation is still far from being